Functional effects of econazole on inducible nitric oxide synthase: production of a calmodulin-dependent enzyme. - Bogle, R. G. (1996)
1. We performed experiments to examine the effects of an anti-fungal imidazole compound, econazole, on the regulation and effects of lipopolysaccharide-inducible nitric oxide synthase (iNOS) activity in rat aortic rings and cultured J774 murine macrophage cells. 2. In endothelium-intact rings of thoracic aorta, phenylephrine caused a concentration-dependent contraction with EC50 of 1.9 +/- 0.15 x 10(-8) M (n = 5). Following incubation with lipopolysaccharide (LPS, 5 micrograms ml-1) for 8 h there was a right-shift in the concentration-response curve (EC50 3.1 +/- 0.28 x 10(-7) M, P < 0.05) with a depression in the maximum contraction from 1.44 +/- 0.25 g to 0.86 +/- 0.26 g (n = 4). Co-incubation of rings with econazole (1 x 10(-5) M) partially inhibited the LPS-induced loss of reactivity to phenylephrine (EC50 6.5 +/- 0.72 x 10(-8) M) and fully inhibited the reduction in maximum tension (1.49 +/- 0.19 g; n = 5). 3. In J774 cells, incubation with LPS (10 micrograms ml-1, 24 h) resulted in significant nitrite production that was inhibited by co-incubation with econazole (IC50 5.0 +/- 0.9 x 10(-6) M; n = 5). In cells stimulated with LPS, production of L-[3H]-citrulline from L-[3H]-arginine was 6.41 +/- 0.22 pmol mg-1 protein min-1 (n = 3). This was inhibited by 92 +/- 6% by addition of NG-monomethyl-L-arginine (L-NMMA, 1 x 10(-3) M; n = 3) to the homogenate but not by econazole (1 x 10(-5) M; n = 3). In contrast pretreatment of cells with econazole (1 x 10(-5) M) markedly reduced the LPS-induced [3H]-citrulline production (0.86 +/- 0.053 pmol mg-1 protein min-1; P < 0.01; n = 3). 4. In cells treated with LPS and econazole, L-[3H]-citrulline production was restored in a concentration-dependent manner by addition of calmodulin (1 x 10(-8)-3 x 10(-7) M) with an IC50 of 4.2 +/- 0.9 x 10(-8) M. 5. We have shown that econazole inhibits the functional and biochemical activity of iNOS in rat aortic rings and cultured J774 cells. Treatment of cells with econazole renders the NO synthase functionally inactive. In econazole-treated cells enzyme activity is restored by calmodulin suggesting that econazole may inhibit the binding of this essential co-factor to the enzyme following its production. These studies may have implications for the design of novel anti-inflammatory agents working through the L-arginine-nitric oxide pathway.